2008
DOI: 10.1002/cbdv.200890127
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Volatiles in Tunisian Populations of Teucrium polium L. (Lamiaceae)

Abstract: Volatiles from wild Tunisian diploid (2n=2x=26) and tetraploid (2n=4x=52) Teucrium polium L. populations from five bioclimatic zones were assessed by GC and GC/MS. Thirty-eight compounds were identified. Main volatiles at the species level were myrcene (6; 15.3%), germacrene D (27; 9.0%), alpha-pinene (6.6%), beta-pinene (3; 5.8%), and alpha-cadinol (38; 5.1%). A significant variation among populations was observed. The tetraploid populations belonging to the sub humid and lower semi arid bioclimates showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…Indeed, Aghakhani et al [57] isolated twenty-two new flavonoid compounds that were first reported for Phlomis species. Our results are in agreement with previous studies that indicated that the Teucrium genus contains different classes of phytoconstituents such as monoterpenes, sesquiterpenes [58], polyphenols, flavonoids [59,60], and fatty acid esters [61,62]. Moreover, flavonoids are polyphenols that are detected in medicinal plants with a wide variety of biological activities [63].…”
Section: Phytochemical Composition Of T Polium Extractsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, Aghakhani et al [57] isolated twenty-two new flavonoid compounds that were first reported for Phlomis species. Our results are in agreement with previous studies that indicated that the Teucrium genus contains different classes of phytoconstituents such as monoterpenes, sesquiterpenes [58], polyphenols, flavonoids [59,60], and fatty acid esters [61,62]. Moreover, flavonoids are polyphenols that are detected in medicinal plants with a wide variety of biological activities [63].…”
Section: Phytochemical Composition Of T Polium Extractsupporting
confidence: 93%
“…Moreover, flavonoids are polyphenols that are detected in medicinal plants with a wide variety of biological activities [63]. Many previous studies have described the presence of various flavonoids such as apigenin, luteolin, rutin, cirsiliol, cirsimaritin, salvigenin, and eupatorin in the roots, aerial parts, and inflorescences of the plant [17,[59][60][61][62][63][64][65][66]. Furthermore, one intermediate in the biosynthetic pathways of alkaloids, iridoid glycoside (Harpagoside), was also detected [60].…”
Section: Phytochemical Composition Of T Polium Extractmentioning
confidence: 99%
“…campestris different essential oil profiles, often characterized by the abundance of β ‐pinene, were also observed . Differences between our results and those previously reported could be attributed to the number of analyzed populations and especially to ecological conditions, phenological stage, and genetic diversity linked mainly to the ploidy level and the species breeding system …”
Section: Resultscontrasting
confidence: 71%
“…Aerial part extracts were known for their anti-inflammatory, antibacterial, antihypertensive, hypoglycemic, hypolipidemic, anorexic and antioxidant activities [9]. The species has been reported for its neo-clerodane diterpenoids and essential oils [16].…”
Section: T Maghrebinum Greuter Et Burdet Is a Species Growingmentioning
confidence: 99%